Behaviours of Atlantic herring and mackerel in a purse-seine net, observed using multibeam sonar. (6th October 2016) - Tenningen, Maria; Macaulay, Gavin J.; Rieucau, Guillaume; Peña, Héctor; Korneliussen, Rolf J.
Abstract : To ensure efficient and sustainable purse-seine fisheries, the catch process must be monitored to better understand the reactions of fish to the gear. In this study, we monitored the behaviours of herring ( Clupea harengus ) and mackerel ( Scomber scombrus ) schools during purse-seine capture using a multibeam imaging sonar (Simrad MS70, 75–112 kHz) mounted on a research vessel. The fish behaviours differed between species and purse-seine sets. For both species, the acoustic volume backscattering coefficient increased as 0–80% of the seine was hauled aboard, indicating a corresponding increase in fish spatial density. This increase was significantly greater for herring than mackerel. As 0–40% of the seine was hauled aboard the fishing vessel, schools changed their spatial distribution and volume independent of seine hauling, while for some schools, depth and height decreased. The acoustic volume backscattering strength was up to 25 dB higher in the centre of the school than in the edges. The average lateral target strength was estimated for individual fish in the captured herring schools, and the effect of incident angle on the backscattering strength is considered.